2018
DOI: 10.1111/jphp.12953
|View full text |Cite
|
Sign up to set email alerts
|

Co-administrating apigenin in a high-cholesterol diet prevents hypercholesterolaemia in golden hamsters

Abstract: This study illustrated that dietary administration of apigenin attenuated HC feeding-induced hypercholesterolemia in hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In another study by Wong et al, apigenin (60 and 300 ppm) was co-administered with a high-cholesterol diet in golden hamsters. Consistent with the findings of the previous study, hamsters fed with apigenin showcased a decrease in serum total cholesterol and triglyceride levels [ 23 ]. Apigenin co-administered with the diet resulted in a protective effect against aortic plaque formation and promoted the fecal elimination of cholesterol.…”
Section: Therapeutic Potential Of Apigenin In Cardiovascular Disorderssupporting
confidence: 91%
“…In another study by Wong et al, apigenin (60 and 300 ppm) was co-administered with a high-cholesterol diet in golden hamsters. Consistent with the findings of the previous study, hamsters fed with apigenin showcased a decrease in serum total cholesterol and triglyceride levels [ 23 ]. Apigenin co-administered with the diet resulted in a protective effect against aortic plaque formation and promoted the fecal elimination of cholesterol.…”
Section: Therapeutic Potential Of Apigenin In Cardiovascular Disorderssupporting
confidence: 91%
“…Various flavonoids have been reported to attenuate the progression of atherosclerosis. Wong et al (2018) showed that API ameliorates hyperlipidemia, a risk factor for atherosclerosis, by reducing cholesterol biosynthesis. Disturbed lipid metabolism in macrophages and foam cell formation are key factors promoting the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Combination index (CI) analysis was performed using the Chou-Talalay method. Western blot analysis was performed as previously described [ 77 , 78 ] using the antibodies tabulated in SI 22 . All functional assays were performed in a medium with 2% FBS.…”
Section: Methodsmentioning
confidence: 99%